2010
DOI: 10.1590/s0034-89102010005000029
|View full text |Cite
|
Sign up to set email alerts
|

Riscos à saúde em áreas próximas a aterros de resíduos sólidos urbanos

Abstract: OBJECTIVE:To evaluate the association between living close to solid waste landfi ll sites and occurrences of cancer and congenital malformations among populations in their vicinity. METHODS:Deaths among people living in the municipality of São Paulo, Southeastern Brazil, between 1998 and 2002 were selected and geocoded, according to selected causes. Over the period evaluated, there were 351 deaths due to liver cancer, 160 due to bladder cancer and 224 due to leukemia, among adults, 25 due to childhood leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 20 publications
2
8
0
9
Order By: Relevance
“…Our study did not report a significant association between dumpsite exposure and cancer, supported by a study conducted for the urban waste dumps in the municipality of São Paulo [25] and a study conducted in Great Britain [26]. A systematic review concluded that there was inadequate evidence to link landfills with the occurrence of cancer [12,19].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our study did not report a significant association between dumpsite exposure and cancer, supported by a study conducted for the urban waste dumps in the municipality of São Paulo [25] and a study conducted in Great Britain [26]. A systematic review concluded that there was inadequate evidence to link landfills with the occurrence of cancer [12,19].…”
Section: Discussionsupporting
confidence: 50%
“…This can lead to infertility, intrauterine death, spontaneous abortion, low birth weight, and congenital anomalies. An ecological study reported that residents living within approximately 3 km of the Nant-y-Gwyddon landfill site in South Wales had a significant two-fold increase of maternal risk of having baby with a congenital abnormality [23]; this finding was supported by a review by Guisti [7], in contrast with a study by Gouveia and do Prado [25]. Golberg et al reported that low birth weight was significantly elevated with the odd ratio of 1.2 among residents living within a 2 km radius from a municipal solid waste landfill in Montreal, Quebec [27].…”
Section: Discussionmentioning
confidence: 94%
“…A study in Brazil evaluated the association between residence close to solid waste landfill sites and cancer mortality. 6 The exposed areas were defined using a 2-km buffer radius around 15 sites. Standardized mortality ratios were analysed in Bayesian spatial models.…”
Section: Discussionmentioning
confidence: 99%
“…Resíduo ou lixo pode ser qualquer material considerado inútil, supérfluo ou sem valor, gerado pela atividade humana, indesejado e descartado no meio ambiente (GOUVEIA & PRADO, 2010). De acordo com a norma brasileira NBR 10.004 (ABNT, 2004a, p. 1), "Resíduos Sólidos, são os resíduos nos estados sólido e semissóli-do, que resultam de atividades da comunidade, de origem industrial, doméstica, hospitalar, comercial, agrí-cola, de serviços e de varrição".…”
Section: Introductionunclassified